Income inequality and economic growth: new evidence from latin america. (2014)
This paper explores the relationship between the inequality of income distributionand the economic growth of 20 Latin American and Caribbean countries duringthe 1980-2010 period. The study shows that the features of this relationship depend on the income level. In general, inequality is harmful to economic growth. However, when it comes to the upper tail of the richer countries’ income distribution, higherinequality encourages economic growth and the relation becomes positive. Thus,contrary to the economic policy recommendations for the richer countries, our evidencesuggests that progressive redistributive policies in favor of poorer layers ofpopulation promote economic growth in lower income economies.